On the Composition of Committees - Klaas J. Beniers; Otto H. Swank (Tinbergen Institute, 2003)
This paper is concerned with the role of committees in collective decision-makingprocesses in a world where agents must be motivated to collect information. Committees improvethe quality of decision-making by providing information and by coordinating the collection ofinformation. We address two types of questions. First, how does the composition of a committeeaffect final decisions? Second, what is the optimal composition of a committee from thedecision maker's point of view? As to the latter question, we show that the cost of informationcollection plays an important role. If this cost is low, then the preferences of the committeemembers should be aligned to those of the decision maker. Members with similar preferences asthe decision maker collect the proper pieces of information. Moreover, manipulation ofinformation does not occur if the preferences of the decision maker and the members areconsonant. If the cost of searching is high, then the committee should be composed ofmembers with polarized preferences. Outliers have a strong incentive to search for information.
Keywords: D81; D83; 330; committees; information collection; preference outliers; moderates.; Entscheidung; Informationsversorgung; Informationsverhalten; Theorie